Robust Self‐Standing Single‐Ion Polymer Electrolytes Enabling High‐Safety Magnesium Batteries at Elevated Temperature. Issue 31 (29th June 2022) - Ge, Xuesong; Song, Fuchen; Du, Aobing; Zhang, Yaojian; Xie, Bin; Huang, Lang; Zhao, Jingwen; Dong, Shanmu; Zhou, Xinhong; Cui, Guanglei
Abstract: Rechargeable magnesium batteries (RMBs) have great potential in the field of high‐temperature specialized batteries owing to the superior thermostability and lower propensity for dendrite formation of Mg metal anodes. And the development of Mg 2+ ‐conducting electrolytes that can operate stably under elevated temperature conditions (>100 °C) is the key to high‐temperature RMBs. Here, a robust self‐standing single‐ion polymer electrolyte (SSPE) enabling high‐safety RMBs working at elevated temperature is presented. This SSPE exhibits an expanded electrochemical stability window of 4.8 V (vs Mg 2+ /Mg), a remarkable Mg 2+ ‐ion transference number of 0.79, and a highly reversible Mg plating/stripping performance. This rationally designed SSPE enables home‐made Mo6 S8 //Mg batteries with superior high‐temperature (up to 150 °C) performance and significantly improved safety characteristics under abuse conditions. This design concept for a robust SSPE provides a promising path to high‐safety specialized RMBs operating at the elevated temperature, which also offers a new path for the development of functionalized electrolytes. Abstract : To exploit high‐temperature specialized batteries, a robust self‐standing single‐ion polymer electrolyte (SSPE) enabling high‐safety rechargeable magnesium batteries at elevated temperature even up to 150 °C is presented. This robust SSPE exhibits an expanded electrochemical stability window of 4.8 V (vs Mg 2+ /Mg), a remarkable Mg 2+ ‐ion transference number of 0.79, and a highly reversible Mg plating/stripping performance.